PENGARUH KUALITAS PELAYANAN PETUGAS BOARDING GATE TERHADAP KEPUASAN PENUMPANG PESAWAT DELAY MASKAPAI CITILINK DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Mirnawati; Arif Fakhrudin (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Regarding service, an important thing that must be paid attention to by the company is passenger service from the check-in or boarding gate service section, because good or bad service will ultimately create an image for the airport and the airline. The method used in this research is quantitative, with a sample size of 100 respondents. The type of sampling technique in this research uses purposive sampling. Then the data was analyzed using validity tests, reliability tests, t tests, coefficient of determination tests. Regarding the service quality of boarding gate officers on the satisfaction of passengers on delayed Citilink Airline flights at Zainuddin Abdul Madjid Lombok International Airport with Ho being rejected, which means that there is an influence on the quality of service of boarding gate officers on the satisfaction of passengers on delayed Citilink Airline flights at Zainuddin Abdul Madjid Lombok International Airport.